2020
DOI: 10.1177/0963689720960190
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Peripheral ERK Signaling Ameliorates Persistent Muscle Pain Around Trigger Points in Rats

Abstract: The purpose of this study was to investigate whether the ERK signaling pathway was involved in ameliorating chronic myofascial hyperalgesia from contused gastrocnemius muscle in rats. We established an animal model associated with myofascial pain syndrome and described the mechanism of muscle pain in an animal model. Changes in the mechanical pain threshold were observed 0.5, 1, 2, 3, 4, 5, 8, 12, 18, and 24 h after ERK inhibitor injection around myofascial trigger points (MTrPs) of the gastrocnemius muscle in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…ERK1 and ERK2 (ERK1/2) belong to an evolutionarily conserved group of serine/threonine protein kinases, and they play important roles in the change of the nervous system in various diseases. Previous studies have reported that phosphorylation of ERK (pERK) is increased in the sensory nervous system in neuropathic pain conditions, resulting in the manifestation of allodynia and hyperalgesia symptoms [ 5 , 6 , 7 , 8 , 9 ]. It has been also reported that inhibiting the ERK is effective in relieving pain in animal models of this neuropathic pain, suggesting the ERK could be an important therapeutic target for the treatment of neuropathic pain [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…ERK1 and ERK2 (ERK1/2) belong to an evolutionarily conserved group of serine/threonine protein kinases, and they play important roles in the change of the nervous system in various diseases. Previous studies have reported that phosphorylation of ERK (pERK) is increased in the sensory nervous system in neuropathic pain conditions, resulting in the manifestation of allodynia and hyperalgesia symptoms [ 5 , 6 , 7 , 8 , 9 ]. It has been also reported that inhibiting the ERK is effective in relieving pain in animal models of this neuropathic pain, suggesting the ERK could be an important therapeutic target for the treatment of neuropathic pain [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we used disposable biopsy instrument (SuperCore™, Argon Medical Devices, Inc.) for MTrPs muscle tissue and performed morphological observations. Hematoxylin and eosin (HE) staining revealed abnormal hypertrophy of skeletal muscle fiber at the MTrPs( Zhang et al, 2020b ; Jin et al, 2020 ; Jin et al, 2020 ; Zhu et al, 2020 ). The muscle fibers in the MTrPs showed annular or elliptical muscle fibers of different sizes in cross-sectional views ( Jin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies proved that the histological hallmark of MTrPs is the abnormal hypertrophy of local skeletal muscle ( Huang et al, 2015 ; Zhang et al, 2020b ; Jin et al, 2020 ; Zhu et al, 2020 ). However, whether MEF2C is involved in MTrPs remain unknown.…”
Section: Introductionmentioning
confidence: 99%